Co-contamination of antimony and arsenic reshapes resistome, virulome, and virome in poultry feces near the world's largest antimony mine - Zhipeng Yin; Yuzhu Zhang; Shanjun Song; Cheng Li; Jianbo Shi; Yongguang Yin; Yong Cai (Environmental Pollution, 2026)

Enhancing nattokinase stability through synergistic interactions:Construction and mechanism analysis of multi-level encapsulation structures in fig-like gel beads - Yao Cheng; Yanjun Tong; Shanjun Tao; Shiqi Zhang; Han Jiang; Ruijin Yang (Food Research International, 2026)

Subseasonal Predictability of the North China Heat Extremes in Dynamical Models - Shanjun Cheng; Jinqing Zuo; Jianshuang Cao; He Huang; Liye He; Qiang Guo; Lijun Bian (Journal of Meteorological Research, 2026)

Distinct dynamical processes of dry and wet heatwaves in North China: observational and modeling perspectives - Shanjun Cheng; Jinqing Zuo; Yu Nie; Jiacan Yuan; He Huang; Liye He (Climate Dynamics, 2026)

Multi-omics integration reveals gut Microbiome and Short-chain fatty acid profiles in gastric cancer cachexia patients and their clinical significance - Hao Liu; Yuxi Cheng; Shanjun Tan; Yidan Qu; Zhige Zhang; Mingyue Yan; Guohao Wu (World Journal of Microbiology and Biotechnology, 2025)

Challenges in Predicting Yangtze River Basin Summer Temperatures: The Role of Atmospheric Circulation and Tropical SST Forcing - Jinqing Zuo; Xiaolong Jia; Tao Feng; Shanjun Cheng; Hui Gao; Xuannan Wang; Li Li; Jingpeng Liu; Jie Tang; Lei Wang (International Journal of Climatology, 2025)
The densely populated and economically crucial Yangtze River Basin (YRB) in China has experienced an increasing trend of high‐temperature events during recent summers, highlighting the importance of skillful seasonal prediction for effective mitigation and adaptation. However, the sources of predictability and origins of prediction errors for YRB summer temperatures remain poorly understood. This study investigates the predictability of YRB summer (July–August) temperatures using hindcasts from three state‐of‐the‐art dynamical climate models to better understand these sources. While all models demonstrate some skill at a 0‐month lead, this capability becomes severely limited at lead times of 1 month or longer. Analysis of the models' ability to simulate the driving physical mechanisms reveals that while they reasonably capture the observed relationship between YRB summer temperatures and the associated local atmospheric circulation pattern linked to a Eurasian mid‐to‐high latitude wave train, significant uncertainties in predicting this wave train itself constrain overall skill. Furthermore, observational evidence shows a significant out‐of‐phase relationship between YRB summer temperatures and concurrent sea surface temperature (SST) anomalies in the equatorial central–eastern Pacific, a relationship that the models fail to reproduce. This failure stems from varying model biases in simulating the atmospheric circulation response to equatorial Pacific SST forcing, hindering their ability to capture the Pacific–YRB teleconnection. Therefore, deficiencies in simulating both the Eurasian circulation and the tropical Pacific forcing significantly contribute to the limited seasonal prediction skill for YRB summer temperatures, underscoring the need for improved representation of mid‐latitude dynamics, tropical air–sea interactions and associated atmospheric teleconnections in dynamical models.

Summer heatwaves in China during 1961–2021: The impact of humidity - Shanjun Cheng; Shanshan Wang; Mingcai Li; Yongli He (Atmospheric Research, 2024)

Spatial patterns of torrential rain in the Haihe River Basin and the corresponding large‐scale circulation - Shanjun Cheng; Mingcong Li; Shanshan Wang; Sujie Liang (International Journal of Climatology, 2024)
The classification of torrential rain is crucial to the flood mitigation and water resources, but the relevant research in the Haihe River Basin (HRB) is lacking. In this study, 156 regional torrential rain events from 1972 to 2022 were classified into two types using cluster analysis: eastern type and southern type. The eastern type is the typical torrential rain in the HRB, accounting for 61.5% of the total days, whereas the southern type mainly occurs in the piedmont plain with larger intensity and scope, which would pose more severe hazards. Corresponding large‐scale circulation patterns of the two types reveal a clear relationship between the HRB torrential rain and ascending motion, associated with the anomalies of low‐level moisture convergence and upper‐level wind divergence. The anomalous upper‐level divergence is accompanied by the northward expansion of South Asian High and intensified westerly jets. In the eastern type, strong low‐pressure anomalies north of Lake Baikal at mid‐level produce anomalous northwesterlies. The cold air from mid–high latitudes encounters enhanced southwesterly moist air accompanied by the northward expansion of Western Pacific Subtropical High (WPSH), resulting in the low‐level moisture convergence. In the southern type, the low‐level anomalous convergence is caused by a relatively weak cyclonic anomaly and significantly strengthened southeasterly moisture from the Pacific. The enhancement of southwesterlies results from the cooperative effect of the remarkably northwesterly WPSH and low‐pressure anomalies in South China Sea. As a whole, the eastern type is the result of convergence of cold air and southwesterly moisture driven by a dipole pattern at mid–high latitudes, whereas the southern type is mainly attributed to the accumulation of abundant southeasterly water vapour. This classification can identify high‐risk areas for torrential rain in the HRB and contribute to the forecast skills of extreme precipitation.

Historical evaluation and projection of precipitation phase changes in the cold season over the Tibetan Plateau based on CMIP6 multimodels - Guodong Wang; Yongli He; Boyuan Zhang; Xiaoxia Wang; Shanjun Cheng; Yongkun Xie; Shanshan Wang; Xiaodan Guan (Atmospheric Research, 2023)

Effect of climate zone change on energy consumption of office and residential buildings in China - Yuehao Chen; Mingcai Li; Jingfu Cao; Shanjun Cheng; Ruixue Zhang (Theoretical and Applied Climatology, 2021)